Internal Control Systems that Affects Auditing Results in View of CPA and Tax Auditor in Thailand - Chodchoy, Pritcha; Jaipiem, Kwanhatai; Sutjasen, Arthit (NEU ACADEMIC AND RESEARCH JOURNAL, 2021)
This research purposes of this study were 1) Studying the internal control system of business that affects the audit results in view of the CPA and Tax Auditor in Thailand and 2) Studying the relationship of the company’s internal control system that affects audit results in view of the CPA and Tax Auditor in Thailand. This study collected data through Google Drive, e-mail, group lines and telephone from a CPA and Tax Auditor in Thailand 752 persons. The statistics used for data analysis were: Frequency distribution, Percentage average and the Standard deviation. The results obtained from the research showed that CPA and Tax Auditor in Thailand mostly are female. Result of the opinion level of the company’s internal control system of the CPA and Tax Auditor in Thailand the overall picture is high level. The aspect with the highest average was control activities. Opinion level of audit results of the CPA and Tax Auditor in Thailand the overall picture is high level. The areas with the highest average are standards and reliability by the company’s internal control system forwarding audit results with statistical significance at the 0.001 level of the CPA is Risk assessment, Control activities, Information and communication and the tracking side. Tax Auditor is Risk assessment and Information and communication.